CHOLPON LITERARY-CRITICAL VIEWS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Study of the literary and critical heritage of Cholpan. Cholpon was a poet, prose writer, playwright, translator, publicist as well as a critic and an art critic with a unique personality. His literary and critical articles are of great importance in the formation of the people's spirituality, in the development of literary and aesthetic taste, and in the development of our fiction. It is difficult to imagine the history of new Uzbek literary studies and literary criticism without Cholpon's literary and critical work.